Generalization of contours using deviation angles and error bands - Gökgöz, T (MANEY PUBLISHING, 2005)
In this paper a new approach for generalization of contours is described. The aim of this approach is to obtain both simplified and smoothed contours lying on a minimum number of characteristic points and inside the error bands. Characteristic points of contours are defined in relation to the skeleton lines of the terrain and determined using the deviation angles at the contour points. Error bands for contours are constructed by means of the steepest slope lines and the mean square planimetric errors at the contour points. The new approach is compared to the Li-Openshaw algorithm according to the experimental testing results.
Keywords: AUTOMATIC EXTRACTION; DIGITIZED CONTOURS; DRAINAGE NETWORKS; ELEVATION DATA; ALGORITHMS; COMPUTER; POINTS; LINES; Geography